2018
DOI: 10.1007/s10661-018-6466-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drought-vulnerable regions in North Korea using remote sensing and cloud computing climate data

Abstract: Drought is one of the most severe natural disasters in the world and leads to serious challenges that affect both the natural environment and human societies. North Korea (NK) has frequently suffered from severe and prolonged droughts since the second half of the twentieth century. These droughts affect the growing conditions of agricultural crops, which have led to food shortages in NK. However, it is not easy to obtain ground data because NK is one of the most closed-off societies in the world. In this situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Many studies using EO data for North Korea have been proposed for monitoring land use and land cover (LULC) over the Remote Sens. 2020, 12, 255 7 of 26 past several decades (for example, [51][52][53][54][55]). Furthermore, a number of government institutes and think-tanks have already established different types of thematic maps in North Korea using EO data (e.g., agricultural maps; deforestation maps; land cover maps, etc.).…”
Section: A Difficult-to-access Region: North Korea In the Contexts Ofmentioning
confidence: 99%
“…Many studies using EO data for North Korea have been proposed for monitoring land use and land cover (LULC) over the Remote Sens. 2020, 12, 255 7 of 26 past several decades (for example, [51][52][53][54][55]). Furthermore, a number of government institutes and think-tanks have already established different types of thematic maps in North Korea using EO data (e.g., agricultural maps; deforestation maps; land cover maps, etc.).…”
Section: A Difficult-to-access Region: North Korea In the Contexts Ofmentioning
confidence: 99%
“…For the disasters whose occurrences can be prevented, the complex disaster simulations based on different disaster models can be run over the Clouds as end services to determine the key causes of the disasters [52] [53]. Accordingly, measures can be prioritized in a particular region for preventing the disaster.…”
Section: Preventionmentioning
confidence: 99%
“…Researchers have relied on risk identification, historical information, monitoring based on data processing and analyses and simulation of processes for preventing the actual occurrences of the disaster such as flood and droughts. The studies by Yu and Kim [52] as well as Jeyaseelan [53] identified the vulnerable regions for possible floods and droughts and helped concerned authorities to take effective measures to prevent the occurrence of the disasters. The historical information about the occurrences of the disasters was emphasized to make effective strategies to prevent the occurrence of flooding events by Wan et al [54] and health issues related disasters by Shen et al [85].…”
Section: Preventionmentioning
confidence: 99%
See 2 more Smart Citations